2014
DOI: 10.4103/2319-4170.132889
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast lymphoma: A single-institute experience in Taiwan

Abstract: Background:Breast is an uncommon location of lymphoma involvement. The most common type of primary breast lymphoma (PBL) is diffuse large B-cell lymphoma (DLBCL). Rituximab is the widely used monoclonal antibody against CD20+ B-cell lymphoma, especially DLBCL. We aimed to analyze the clinical features, prognostic factors, and treatment outcome with or without rituximab in primary breast DLBCL. Methods:We retrospectively analyzed patients diagnosed with PBL from October 1987 to March 2012 in our hospital, exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…At 10 years, actuarial OS was 50%, 50% and 76%, respectively (p<0.01) (Aviles et al, 2005). A positive impact of CMT +/-rituximab in PBL was also suggested in the more aggressive DLBCL subtype (Ou et al, 2014;Radkani, Joshi, Paramo, & Mesko, 2014).…”
Section: Ii23 Treatmentmentioning
confidence: 90%
See 1 more Smart Citation
“…At 10 years, actuarial OS was 50%, 50% and 76%, respectively (p<0.01) (Aviles et al, 2005). A positive impact of CMT +/-rituximab in PBL was also suggested in the more aggressive DLBCL subtype (Ou et al, 2014;Radkani, Joshi, Paramo, & Mesko, 2014).…”
Section: Ii23 Treatmentmentioning
confidence: 90%
“…The role of CNS prophylaxis in PBL is controversial. Case series have reported a high incidence of CNS recurrence at 5-17% or even higher if Burkitt's lymphoma was included (Ou et al, 2014;Ryan et al, 2008).…”
Section: Ii23 Treatmentmentioning
confidence: 99%
“…Our study showed that relapse involving the CNS was a major cause of treatment failure for PB‐DLBCL patients, with a 5‐year cumulative CNS relapse incidence of 11.1%. Previous studies reported that CNS relapse occurred in 5%–17% of patients with PB‐DLBCL, and breast involvement is generally considered a high‐risk factor for CNS relapse 5,10,15,17,27,28 . Therefore, CNS prophylaxis is recommended for PB‐DLBCL by some guidelines 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that CNS relapse occurred in 5%–17% of patients with PB‐DLBCL, and breast involvement is generally considered a high‐risk factor for CNS relapse. 5 , 10 , 15 , 17 , 27 , 28 Therefore, CNS prophylaxis is recommended for PB‐DLBCL by some guidelines. 28 However, several retrospective series showed that IT prophylaxis did not decrease CNS relapse risk in patients with PB‐DLBCL.…”
Section: Discussionmentioning
confidence: 99%